Aktualisasi Nilai-Nilai Ahlussunnah Wal Jamaah An-Nahdliyah dalam Membentuk Akhlaqul Karimah - Nindya Pratiwi Putri M; Rofiatul Hosna; Khoirotul Idawati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is motivated by the prevalence of extreme incidents in the field of education, such as bullying, student brawls, and the spread of free association, which have tarnished the reputation of educational institutions. By integrating Aswaja (Ahlussunnah wal Jamaah) values, educational institutions can shape students who contribute positively to the development of science and technology while adhering to Islamic principles in their daily lives. This study employs a qualitative descriptive research design. The data collection techniques used include three methods: observation, interviews, and documentation. To ensure data validity, source triangulation was applied. The data analysis follows the Miles and Huberman model, consisting of data reduction, data presentation, and drawing conclusions. The aims of this research are 1) to actualize the values of Aswaja An-Nahdliyah in shaping students' noble character at SMA Trensains Tebuireng Jombang. 2) to identify the supporting and inhibiting factors in the process of actualizing Aswaja An-Nahdliyah values in shaping students' noble character at SMA Trensains Tebuireng Jombang. Based on the research findings, it can be concluded that the Aswaja values actualized at SMA Trensains Tebuireng include tawasuth, tasamuh, tawazun, i’tidal, and amar ma’ruf nahi munkar. These values are reflected in curriculum integration, extracurricular activities, organizational development, etc. The supporting factors include the localized environment of SMA Trensains Tebuireng, the uniformity of Aswaja NU understanding, and teachers consistently fostering enjoyable learning experiences. Meanwhile, the inhibiting factors are the negative influence of external environments, high achievement targets, and the separation of female dormitories from room supervisors.